2015
DOI: 10.18203/2320-6012.ijrms20150813
|View full text |Cite
|
Sign up to set email alerts
|

A study of risk factors in young patients of myocardial infarction

Abstract: The prevalence of coronary artery disease (CAD) has progressively increased in India during the later half of the half century and is the major cause of morbidity and mortality burden in the world. Global burden of disease study estimate that by the year 2020, the burden of atheroembolic cardiovascular disease in India would surpass that in any other region in the world. 1 Young patients with CAD are specific subset of population requiring attention. Although uncommon entity, it constitutes an important proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…The mean age of young patients with MI in this study was found to be 35.00±4.67 years. Similar age distribution was also reported by the authors such as Akram et al,15 and Deora et al16…”
supporting
confidence: 88%
“…The mean age of young patients with MI in this study was found to be 35.00±4.67 years. Similar age distribution was also reported by the authors such as Akram et al,15 and Deora et al16…”
supporting
confidence: 88%
“…Young adults showed lower incidence of in hospital death in comparison to older adults (1% VS 4%). [6,[37][38][39][40][41]. Otherwise, there were observed no significant differences between young and old adults regarding post AMI complications and this reflects the equal provided high care services provided to all patients in our center.…”
Section: B: In-hospital Complication and Mortalitymentioning
confidence: 92%
“…The combined sample size of the studies was 32,585 cases, comprising 26,020 males and 6,564 females. It is worth noting that the smallest sample size was from the study conducted by Akram et al, [16] with only 50 cases, while the study by Keri et al [13] had the largest sample size, with 29,515 cases. This variation in sample size suggests that there may be differences in the prevalence of AMI across different populations.…”
Section: Study Characteristicsmentioning
confidence: 94%
“…All six studies were published in peer-reviewed journals, suggesting that they met adequate quality standards for scientific literature. These studies were conducted in various countries, including the USA & Canada [13], Australia [14], France [15], India [16], Trinidad [17], and Iran [18], suggesting a global reach and potential generalizability of findings to populations worldwide. Overall, the quality and diversity of the included studies indicate a comprehensive review of the prevalence, incidence, and risk factors of MI in different regions of the world.…”
Section: Study Characteristicsmentioning
confidence: 99%